DEVELOPMENT OF POPULAR SCIENTIFIC BOOKS ON THE POPULATION STRUCTURE OF RAMBAI PADI (SONNERATIA CASEOLARIS L.) ON THE BANKS OF THE ALUH ALUH - Febrianti, Nur Ervina; Dharmono, Dharmono; Utami, Nurul Hidayati (Universitas PGRI Sumatera Barat, 2024)
The population structure is a study in ecology that discusses the existence of a group of plants in a particular area. Rambai padi, found along the banks of Aluh Aluh River, Simpang Warga Village, Banjar Regency has the potential as a source of local potential-based teaching materials in the form of a popular scientific books. This research aims to describe the population structure of rambai padi, describe the process of developing a popular scientific book, and assess the feasibility of such a book. This research uses the Research and Development method using the Plomp & Nieveen (2013) which consists of three phases: preliminary research, prototyping phase, and assessment phase with research subjects by two experts as validators and five students as readability test subjects. The results showed that the population structure of the rambai padi plants obtained the number in the pre-reproductive phase amounted to 36,86 ind/ha, the reproductive phase amounted to 28,79 ind/ha, and post-reproductive phase amounted to 12,50 ind/ha, resulting that the pyramid shape obtained was a pyramid with a wide base shape. The Popular Scientific titled